Community Awareness and Attitudes towards Influenza Outbreak and Prevention in Serian, Sarawak. - Rohaya Mohd Nor,; Rose Nanju@Manju,; Samuel Lihan,; Sidiah John Siop,; Rekaya Vincent Balang,; Constance Rinen Justin Wah,; Nordiana Nordin, (Universiti Kebangsaan Malaysia, 2013)
To date, there has been no systematic research that investigates the rural community awareness and attitudes towards pandemic influenza H1N1 and its prevention measures in the context of Sarawak.